Mental health condition among female workers during COVID-19 pandemic: insights from Dhaka city, Bangladesh - Shindaini, Al Jamal Mustafa; Alam, Towheedul; Siddiqua, Fahima; Saha, Shantanu Kumar (Intelektual Pustaka Media Utama, 2024)
The coronavirus illness 2019 (COVID-19) created previously unheard-of vulnerabilities in people's physical and mental health situations worldwide. The study aims to evaluate the mental health conditions among a representative sample of female workers in Dhaka city, Bangladesh during the COVID-19 pandemic and its effect on their state of sleep and its patterns as well as their professional lives. A cross-sectional quantitative method along with structural questionnaires was designed. Data collection was conducted through an online survey, and responses were received from 112 respondents. The Depression Anxiety Stress Scales 21 (DASS-21) was used to assess the depression, anxiety, and stress levels of the respondents. The result shows that the respondents had depression, anxiety and, stress, respectively. Also, 52.50% of the respondents were dissatisfied with their sleeping patterns during the pandemic. After conducting a Chi-square test, the study also revealed that the respondents who had issues with depression, anxiety, and stress also had difficulties with the longer duration of staying at home (p<0.05), concentrating on their work (p<0.05), and working from home (p<0.05). The test also showed a significant relationship between the respondents' socio-demographic features and deteriorated mental health conditions. The study identifies that COVID-19 pandemic has clear impact on female worker’s mental health and their professional life.